Efficient Android‐based storage encryption using multi‐core CPUs. Issue 18 (7th February 2017) - Alomari, Mohammad Ahmed; Samsudin, Khairulmizam; Ramli, Abdul Rahman; Hashim, Shaiful J.
Abstract: The huge proliferation of mobile and handheld devices, such as tablets and Smartphone devices, has come with different threats to the sensitive data and personally identifiable information stored inside these devices. The most efficient way to ensure data protection is through encryption; however, it comes with great impact on these small gadgets, which suffer from limited resources. Majority of recent mobile devices are equipped with increasingly powerful multi‐core processors that researchers can leverage in order to enhance data protection while maintaining proper device performance. In this paper, we introduce a parallel implementation for data encryption inside the storage of Android‐based mobile devices. This work implements a multi‐core design of different encryption ciphers, making use of the commodity multi‐core CPUs available currently in new smart gadget devices, in order to enhance the performance inside these resource‐limited devices. Ciphers XTS‐AES, XTS‐Twofish, and XTS‐RC6 are used during the experiments; however, the main focus is given to XTS‐AES because it is developed specifically for storage encryption. Parallel encryption experiments are conducted on a mobile device, and performance comparisons are presented. The parallel XTS‐AES has shown a maximum performance speedup of 1.71, with 86% efficiency, faster than the serial counterpart, with higher encryption throughput in the device up to 8290 and 11 380 KB/s when using XTS‐AES and XTS‐RC6 ciphers, respectively. In addition, we performed comparison between mobile device and desktop machine using similar experimental setup. It shows that the performance of storage encryption in mobile devices still lags by more than 10 folds when compared with desktop environment. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : We introduce a multi‐core design implementation for data encryption inside the storage of Android‐based mobile devices using an NIST certified crypto algorithm. Parallel encryption experiments are conducted on a mobile device and performance is evaluated. The parallel XTS‐AES shows a performance speedup of 1.71 faster than the serial counterpart; with higher encryption throughput in the device up to 8290 and 11 380 KB/s when using XTS‐AES and XTS‐RC6 ciphers, respectively. Mobile–desktop experiments show that mobiles still lag by 10 folds.